2015
DOI: 10.1002/ejoc.201500800
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Efficient Copper(I)‐Catalyzed Cascade Reaction of o‐Alkenylphenyl Isothiocyanates with Isocyanides Leading to 5H‐Benzo[d]imidazo[5,1‐b][1,3]thiazines

Abstract: The highly efficient copper(I)-catalyzed cascade reaction of (E)-3-(2-isothiocyanatophenyl)acrylates and (E)-3-(2-isothiocyanatophenyl)acrylonitriles with isocyanides was explored. The method provides an expedient route for the syn- ,3]thiazines in good to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The present ortho -alkenylation/annulation sequences provide straightforward synthetic routes toward such classes of compounds. It is also noted that o -aminocinnamates like compounds 3′ have also been transformed to not only indoles and quinolines ,, but also other nitrogen-containing fused heterocyclic compounds including indoloquinoline, isoquinolonoquinazoline, chromenoquinoline, and benzoimidazothiazine derivatives …”
mentioning
confidence: 99%
“…The present ortho -alkenylation/annulation sequences provide straightforward synthetic routes toward such classes of compounds. It is also noted that o -aminocinnamates like compounds 3′ have also been transformed to not only indoles and quinolines ,, but also other nitrogen-containing fused heterocyclic compounds including indoloquinoline, isoquinolonoquinazoline, chromenoquinoline, and benzoimidazothiazine derivatives …”
mentioning
confidence: 99%
“…Similar reaction conditions were used by this group for developing the method of synthesis of 5H‐benzo[ d ]imidazo[5,1‐ b ]‐[1,3]thiazines 83 by copper(I) chloride cascade reaction of o ‐alkenylphenyl isothiocyanates 82 with isocyanides 1 (Scheme 43). [ 54 ]…”
Section: [3+2]‐cycloaddition Of Activated Methylene Isocyanidesmentioning
confidence: 99%
“…4 Recently, we and others have reported tandem reactions as novel routes to attractive heterocyclic scaffolds. 5 The targets of studies reported here are amino-functionalized benzo[4,5]imidazo[2,1– a ]isoquinoline and isoquinolino[3,4– b ]-quinoxaline cores as they appear in many bioactive compounds possessing antitumor, anticancer, antibacterial, antituberculosis, and antimalarial activities. 6…”
mentioning
confidence: 99%
“…These strategies employ atom- and step-economical transformations to introduce structural complexity by allowing multiple bond-forming events to occur in one transformative operation . Recently, we and others have reported tandem reactions as novel routes to attractive heterocyclic scaffolds . The targets of studies reported here are amino-functionalized benzo­[4,5]­imidazo­[2,1- a ]­isoquinoline and isoquinolino­[3,4- b ]­quinoxaline cores as they appear in many bioactive compounds possessing antitumor, anticancer, antibacterial, antituberculosis, and antimalarial activities …”
mentioning
confidence: 99%